Cells and Biomaterials in Regenerative Medicine - Eberli, Daniel (IntechOpen, 2014)
This book serves as a good starting point for anyone interested in the application of tissue engineering. It offers a colorful mix of topics, which explain the obstacles and possible solutions for TE applications. The first part covers the use of adult stem cells and their applications. The following chapters offer an insight into the development of a tailored biomaterial for organ replacement and highlight the importance of cell-biomaterial interaction. In summary, this book offers insights into a wide variety of cells, biomaterials, interfaces and applications of the next generation biotechnology, which is tissue engineering.